2022
DOI: 10.1177/26335565221081288
|View full text |Cite
|
Sign up to set email alerts
|

Definition of patient complexity in adults: A narrative review

Abstract: Background Better identification of complex patients could help to improve their care. However, the definition of patient complexity itself is far from obvious. We conducted a narrative review to identify, describe, and synthesize the definitions of patient complexity used in the last 25 years. Methods We searched PubMed for articles published in English between January 1995 and September 2020, defining patient complexity. We extended the search to the references of the included articles. We assessed the domai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 96 publications
1
49
0
Order By: Relevance
“…SLENQ is specialized for patients with systemic lupus erythematosus. Nicolaus et al (2022) reviewed definitions of patient complexity, which included complexity defined with complexity measurement tools or conceptual models [ 11 ]. They concluded that there exists considerable heterogeneity in definition of patient complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SLENQ is specialized for patients with systemic lupus erythematosus. Nicolaus et al (2022) reviewed definitions of patient complexity, which included complexity defined with complexity measurement tools or conceptual models [ 11 ]. They concluded that there exists considerable heterogeneity in definition of patient complexity.…”
Section: Discussionmentioning
confidence: 99%
“…We searched two databases MEDLINE and CINAHL (see Supplementary S1 for search terms and search string). We also checked references from prior systematic reviews [ 11 , 12 , 13 ], and searched for references in the articles identified for inclusion, using Web of Science. If a study was not indexed in Web of Science ( ) (Accessed on 30 June 2022), we used Citationchaser [ 18 ] or Google scholar ( ) (Accessed on 30 June 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, not only the number of simultaneous chronic diseases influences health but also the severity of them added to several psychosocial factors ( 15 ). Complexity could be understood as a dynamic state in which socioeconomic, cultural, environmental, behavioral, and biological aspects operate as factors that hinder the understanding and management of health in certain people ( 16 ). Consequently, the interrelation between different factors may lead to interactions of diagnostic procedures or interventions, different treatment strategies, and multiple healthcare ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complexity could be understood as a dynamic state in which socioeconomic, cultural, environmental, behavioral, and biological aspects operate as factors that hinder the understanding and management of health in certain people ( 16 ). Consequently, the interrelation between different factors may lead to interactions of diagnostic procedures or interventions, different treatment strategies, and multiple healthcare ( 16 ). That is why we distinguished between the complexity of the case, which refers to overlapping diseases and symptoms, and the complexity of care, which refers to the provision of healthcare and the joint involvement of systems and specialties.…”
Section: Introductionmentioning
confidence: 99%